Kewenangan Presiden Dalam Pengangkatan Panglima TNI Ditinjau Dari Sistem Presidensial - Arsyad, Dea (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Gunung Djati Bandung, 2024)
Abstrack; The Presidential system ensures a strong position for the President in Indonesia's state system. However, in the derivative regulations of the 1945 Constitution, the position of the DPR (People's Consultative Assembly) is stronger than that of the President, as seen in the appointment of state officials. The Law No. 34 of 2004 regarding the Indonesian National Armed Forces (TNI) requires